Pemicuan dan Edukasi Masyarakat Tentang Pemananfaatan Sampah Organik Menjadi Pupuk Organik di Desa Pengudang Kecamatan Teluk Sebong Kabupaten Bintan Tahun 2022 - Simbolon, Veronika Amelia (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Garbage is a complex problem and is one of the sanitation problems in the Pengudang Village area. Waste management is carried out by littering or throwing into the sea and burning dry waste. This has the potential to be a source of environmental pollution for the Pengudang Village community. Organic waste that is processed properly and correctly, will improve the quality of the environment and can even increase family income. The purpose of community service is to provide education to the residents of Pengudang Village about the use of organic waste so that they can increase the knowledge and understanding of residents on how to manage household waste. The implementation method consists of the preparation stage, activity plan, activity implementation stage, implementation method and activity relevance. The results of the activity showed that the participants enthusiastically participated in the presentation of socialization material on the use of waste to the implementation of the simulation of making organic fertilizer. Participants in the socialization were involved directly in the process of making organic fertilizers. The fertilizer that has been made is applied to the plants around the residents' houses. Through this community service activity, participants gain knowledge and skills in utilizing household organic waste into organic fertilizer. Management of household waste is the main objective of the activity, so that the residents of Pengudang Village are able to manage household waste independently. The active role of the government is needed in providing intense education to the community so that waste can be controlled starting from the source of the waste